STUDI PERENCANAAN TPA BULUMINUNG KABUPATEN PENAJAM PASER UTARA DENGAN SISTEM SANITARY LANDFILL - Diharto, Diharto (Jurnal Teknik Sipil dan Perencanaan, 2009)
Development TPA Buluminung Penajam Paser Utara District East KalimantanProvince is planned in accordance with the technology and rules applicable legislation.Planning TPA Buluminung in accordance with the characteristics of the location and theexisting budget system selected sanitary landfill generation III according to the wetclimate, but can not be used on an ongoing basis (not sustainable). This TPA serves 4district is District Penajam, Waru, Babulu and Sepaku. Land area available Â± 18.9 ha.Planning TPA Buluminung sanitary landfill system include: entrances and facilities onsite; tread base waterproof coating; leachate management, management of drainage atthe site; and gas management. The division of land according to the plan is operationalroad infrastructure 2457 m2; office area, garage, workshop 3901 m2; wastewatertreatment plant facilities 642 m2, 36,434 m2 of solid waste disposal area (there are 4zones); zone buffer; zone of the development TPA phase I; zone development TPAphase II; and sludge treatment area installations. Of the land area of 36,434 m2 of landfillwaste can accommodate up to 20 years into the future. Planning TPA Buluminungsanitary landfill system is in conformity with the mandate of the Government RegulationNo. 16 of 2005. Recommended a gradual development TPA Bulumining